Understanding and Addressing Workplace Violence Against Hospital and Emergency Workers - Faisal Ahmad Abdullah Alokasi; Yahya Mustafa Yahya Sweid; jaber mustafa yahya suwayyid; Majed Qassem Ibrahim Masoud; Fatima Ahmed Ibrahim Mashafa; Faten Musa Ibrahim Al-Jaafari; Mohammed Mousa Ahmed Muharraq; Abdulrahman Ali Nahari; Ibrahim Mohammed Tawashi; Atiah Abdullah Ahmed Zaghfi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Violence is a common hazard faced by healthcare workers. Healthcare workers report more workplace violence injuries than workers in any other industry and are significantly more likely than other workers to experience violence. Healthcare and social service workers are the largest group of workers at risk for violence. Workers singled out as particularly vulnerable to violence are those who work in emergency departments. Violence is such a serious problem in the healthcare industry that regulations specifically concerning violence against healthcare workers have been established. Two major consequences of workplace violence are physical injuries and psychological trauma. Physical injuries, including lacerations and concussions, can sometimes prove to be fatal. Psychological trauma, which can result from even attempted violence, can have serious long-lasting effects. Workers who are severely physically and psychologically traumatized may be unable to work for long periods or may even leave healthcare work altogether. Staffing shortages in healthcare mean that there are not nearly enough nurses to fill severe shortages in the nursing workforce. In addition, injury and trauma in nurses tie up other healthcare workers, including physicians and other nurses, who are necessarily diverted from scheduled work to fill in for their absent colleagues. Finally, healthcare workers who were recently assaulted are more likely to be assaulted again. Therefore, physical and psychological trauma are not only important outcomes of workplace violence in hospitals and emergency rooms; they also help perpetuate that violence. Methods : To explore the current status of workplace violence against hospital and emergency workers, we conducted a comprehensive review of recent research. To identify the surveys and studies about physical assaults, violence, and behaviors against healthcare workers, a systematic literature review was performed from publications in English in various databases. The database search returned 52 articles, from which we extracted the following information: study year, data collection period, country, type of study, sample size, objective, definition of workplace violence, rate of workplace violence, type of violence, and intervention. Conclusion: The topic of workplace violence against health professionals represents a new field for policy-relevant research in the area of labor relations and the quality of healthcare. State and federal statutes have found it necessary to address hospital workplace violence using specific criminal punishment. Private labor arbitrators who have advantages of flexibility with striking judges enforce contractual provisions promoting safe workplaces. Intuitive attention permits the design of a modest policy to protect health professionals from violence by hospital patients. Furthermore, the management style of the physician affects the probability that the patient will be violent towards other workers. Given the availability of information, the policy solution commands broad-based support. Yet modest results may still prove difficult to achieve. The combination of the adversarial interests makes success anything but certain. Clearly, more focused and better research is essential to addressing this ever-present danger.